O Teorema de Pitágoras e algumas aplicações - MAGALHÃES, Carlos Eduardo Costa (Universidade Federal do Tocantins, 2023)
In this course conclusion work, the Pythagorean theorem and some applications with the role of facilitating interaction in school and social daily life and showing how it transformed society giving new characteristics and problem solutions are presented. Initially notes are placed that show us the importance of Geometry for the development of humanity mainly in the initial series, and also a little of the history of Pythagoras, which for many is nothing more than legends / myths of the time. In the sequence, some demonstrations of the theorem will be described based on the thinking of great authors. The applications presented are examples used in school education and in the daily lives of people, so that they clarify the ideas based on the resolutions presented in the course of this study. With this help the students and bring concrete guidance on the Pythagorean theorem, as shown, how it applies, and that serves as a source of research.